Comparison of the application of co- and cross-polarized sentinel-1 synthetic aperture radar data to tropical cyclone evaluation. Issue 3 (4th March 2021) - Zhu, Lin; Geng, Xupu; Xie, Ting; Hu, Liping; Yan, Xiao-Hai
ABSTRACT: Spaceborne synthetic aperture radar (SAR) is considered one of the most powerful sensors for tropical cyclone assessment. In this study, 14 tropical cyclone (TC) events captured by the Sentinel-1A/B satellite are collected to compare the similarities, differences and quantitative relationships between co- and cross-polarization SAR applications for tropical cyclone evaluation. This study uses multiple co-polarized C-band geophysical model functions (GMFs) and cross-polarized ocean backscatter models, including a C-band Cross-Polarized Ocean Backscatter (C-2PO) model and a C-band Cross-Polarization Coupled-Parameters Ocean (C-3PO) model to estimate the sea surface tropical cyclone wind field. The results reveal that the structure values of the wind circle radius by co-polarization SAR wind inversion are similar to those of cross-polarization. The combination of the two polarization modes can get a more accurate estimation on tropical cyclone rating of the intensity level and hazard of the potential tropical cyclone damages. In addition, a corresponding formula with a correlation coefficient of 0.677 between co- and cross-polarization at 10-km resolution is obtained.